Examination of mental well-being levels of individuals who are studying at university and who are receiving compulsory physical education according to different variables - Ünal Türkçapar; Yavuz Yasul (Technium Social Sciences Journal, 2020)
The aim of this research is to investigate the mental well-being levels of individuals who are educated in university preparatory classes according to different variables. In the research, a descriptive screening model has been used. The study group consists of male and female participants in preparatory classes at Kyrgyzstan Turkey Manas University in the 2019-2020 academic year. To evaluate the Mental Well-Being level, "Personal Information Form" prepared by the researcher and the data of the research, "Mental Well-Being Scale", a scale -original name being "Warwick-Edinburgh Mental Well-Being Scale" -developed by Tennant and his fellows (2007) adapted to Turkish by Keldal (2015) was used. Independent Samples T Test for frequency distributions, normality analyses and binary group comparisons, and one way ANOVA test for more than two group comparisons were conducted to provide descriptive information about the participants. As a result, there has been no significant difference in the answers given to questions such as gender, age and division variables, number of close friends, who help you the most when you encounter a problem, which sport branch you are engaged in, who encouraged you to exercise, how long you spend on your daily workouts, and specify some of your reasons to exercise. However, it has been determined that there is a meaningful difference in the answers given to the question of how long you have been playing this sport.